Voltage-dependent intracellular pH in Helix aspersa neurones. - Meech, R W (1987)
1. The intracellular pH (pHi) of large nerve cells from the mollusc, Helix aspersa, was measured with pH-sensitive micro-electrodes. Cells were held under voltage clamp and the effect on pHi of different holding potentials was determined. 2. Depolarization of the cell from the resting potential (about -50 mV) to -10 mV produced a fall in pHi that could be reduced by bathing the cell in nominally Ca2+-free saline. 3. At positive holding potentials pHi increased to a steady level that depended upon the electrochemical gradient for H+ across the cell membrane; it shifted by about 1 unit when the external pH was increased from 7 to 8 (or when the membrane potential increased by 58 mV, Thomas & Meech, 1982). 4. The depolarization-induced increase in H+ permeability was insensitive to SITS (4-acetamido-4'-isothiocyanostilbene-2,2'-disulphonic acid, 20 microM), which blocks pHi regulation at the resting potential in these cells (Thomas, 1976). When pHi was displaced from a steady level by ionophoretic injection of HCl, there was a rapid recovery at depolarized potentials even in the presence of SITS. The H+ pathway appeared to be little affected by prolonged periods at positive membrane potentials. 5. The depolarization-induced H+ efflux was insensitive to the metabolic inhibitor CCmP (carbonyl cyanide-m-chlorophenylhydrazone, 20 microM) and persisted in cells bathed in pH-buffered n-methyl glucamine-gluconate. It was also insensitive to DCCD (N, N'-dicyclohexylcarbodiimide, 10-100 microM) and oligomycin (2-10 micrograms/ml). 6. The H+ pathway could be fully blocked by 1 mM-ZnCl2, 1 mM-LaCl3, 1 mM-CuCl2, 2 mM-CdCl2 or 10 mM-CoCl2. Other divalent ions such as BaCl2 (10 mM) produced a block at membrane potentials near 0 mV but the block was released at more positive potentials. Low levels of LaCl3 (0.1 mM), the organic Ca2+ channel antagonist D600 (100 mg/ml) and high levels of the K+ channel blocker TEA (50 mM) all had similar effects to Ba2+. 7. The K+ channel blocker 4-aminopyridine (10 mM), which blocks H+ currents in perfused Lymnaea neurones (Byerly, Meech & Moody, 1984), has a complex action.(ABSTRACT TRUNCATED AT 400 WORDS)